Upaya Peningkatan Prestasi Belajar Peserta Didik dengan Pengembangan Fasilitas Belajar.Id Google Sites sebagai Sumber Media Belajar Interaktif dalam Mendukung Hybrid Learning - Hariyanto Hariyanto; Marsono Marsono; Didik Dwi Prasetya (Jayapangus Press, 2023)
Merdeka curriculum, ideally required educators to be able to present the content of learning material into interactive innovation in learning media so that the learning process runs well and the quality of students' competence increases. Some free features of the Belajar.id accounts, such as Google Sites, are still not utilized optimally. This research aims to increase student learning achievement by developing Fasilitas Belajar.id Google Sites as a source of interactive learning media to support hybrid learning. The data collection instrument used was a questionnaire with closed questions. The data analyzed is quantitative and qualitative, which contains suggestions from the validator. This research uses the type of Research and Development (R&D). The model used is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The results show that the development of Google Sites Learning. Id facility is a valid, practical, effective learning resource, supports Hybrid Learning and the questions meet the difficulty level requirements and have differentiating power. The post-test results showed that the average of the experimental group was greater than the control group. The independent t-test results show an influence of media use on increasing learning achievement with p<0.05. The development of the Fasilits Belajar. id Google Sites as a source of interactive learning media to support Hybrid Learning can improve student learning achievement.